2015
DOI: 10.1007/s40840-015-0207-0
|View full text |Cite
|
Sign up to set email alerts
|

Neighbor Sum Distinguishing Edge Colorings of Graphs with Small Maximum Average Degree

Abstract: A proper edge-k

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Later, Gao et al [9] showed that if G is a normal graph with ( ) [11] proved that if G is a normal graph with ( )…”
Section: Introductionmentioning
confidence: 99%
“…Later, Gao et al [9] showed that if G is a normal graph with ( ) [11] proved that if G is a normal graph with ( )…”
Section: Introductionmentioning
confidence: 99%